2023
DOI: 10.11158/saa.28.9.6
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific variation in Storchia pacifica (Summers) (Trombidiformes: Stigmaeidae), a widespread species intercepted by Australian biosecurity from seventeen countries

Owen D. Seeman,
Jennifer J. Beard,
Jurgen Otto

Abstract: Storchia pacifica (Summers, 1964) is redescribed from specimens intercepted by staff of the Australian Department of Agriculture, Fisheries and Forestry from Cambodia, Fiji, India, Indonesia, Kiribati, Laos, Pakistan, Papua New Guinea, New Zealand, Nigeria, Samoa, Singapore, Solomon Islands, Tonga, Uganda, Vanuatu, and Vietnam. Most of the specimens were intercepted on products made from woven natural fibre such as mats and baskets. The specimens show variation in the form of their dorsal setae, which are slen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
0
1
Order By: Relevance
“…3). Although the case of asymmetry detected in this study is reported for the first time, asymmetrical variations of other body setae are actually common in mites (Bingül et al 2018;Seeman et al 2023).…”
Section: Species List Of Raphignathidaecontrasting
confidence: 43%
“…3). Although the case of asymmetry detected in this study is reported for the first time, asymmetrical variations of other body setae are actually common in mites (Bingül et al 2018;Seeman et al 2023).…”
Section: Species List Of Raphignathidaecontrasting
confidence: 43%